A first in human clinical trial assessing the safety and immunogenicity of transcutaneously delivered enterotoxigenic Escherichia coli fimbrial tip adhesin with heat-labile enterotoxin with mutation R192G. Issue 45 (21st October 2020) - Riddle, Mark S.; Maciel, Milton; Porter, Chad K.; Poole, Steven T.; Gutierrez, Ramiro L.; Gormley, Robert; Laird, Renee M.; Sebeny, Peter J.; Dori, Kathleen E.; Greenleaf, Melissa E.; Hoq, Fahmida; Turiansky, George W.; et al.
Abstract: Enterotoxigenic Escherichia coli (ETEC) is a leading cause of diarrhea among travelers and pediatric populations worldwide. The tip-localized adhesin of colonization factor antigen (CFA)/I fimbriae was engineered as a donor strand complemented variant (dscCfaE) and delivered via transcutaneous immunization. Preclinical vaccine testing demonstrated safety, immunogenicity and efficacy. A series of open-label dose-escalating phase 1 studies evaluated a 3-dose (days 0, 21, 42) regimen via a transcutaneous skin patch. A total of forty-six subjects were enrolled into one of four vaccine dose levels (10, 50, 250, or 1250 µg) co-administered with single-mutant heat-labile enterotoxin (LTR(192G)). At the 50 µg dose level, ten subjects received the dscCfaE vaccine without LT(R192G). The vaccine was well tolerated with mild local vaccine site reactions characterized by an erythematous papular rash and pruritus, which were less frequent and reactive in the group not receiving LT(R192G). The frequency of responses to dscCfaE were moderate, whereas anti-toxin responses (serum IgA/IgG) ranged from 75 to 100% across groups that received LT(R192G). Antigen-specific antibody-secreting cell responses were elicited at all dose levels, but were generally low. Follow-on studies will optimize construct and route of delivery and assess efficacy in an ETEC challenge study.